2017
DOI: 10.1038/s41598-017-15342-4
|View full text |Cite|
|
Sign up to set email alerts
|

Essential role of mitochondrial Stat3 in p38MAPK mediated apoptosis under oxidative stress

Abstract: Stat3 is an oncogene, frequently associated with malignant transformation. A body of evidence implicates that phospho-Stat3Y705 contributes to its nucleic translocation, while phospho-Stat3S727 leads to the accumulation in mitochondria. Both are of importance for tumor cell proliferation. In comparison to well-characterized signaling pathways interplaying with Stat3Y705, little is known about Stat3S727. In this work, we studied the influence of Stat3 deficiency on the viability of cells exposed to H2O2 or hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…Our study demonstrated that loss of AIBP persistently increased phosphorylation of p38 and ERK1/2 in the retina. p38 is phosphorylated in response to cytokines and oxidative stress [ 79 , 80 ] and activation of the p38 signaling pathway leads to mitochondrial dysfunction and inflammatory responses [ [81] , [82] , [83] , [84] ]. Because a p38 inhibitor blocks mitochondrial dysfunction and inhibits cytochrome c release [ 85 ], it is likely that retinal AIBP not only plays a role in the stabilization of mitochondrial proteins, but also inhibits stress-activated intracellular signaling responses, such as p38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that loss of AIBP persistently increased phosphorylation of p38 and ERK1/2 in the retina. p38 is phosphorylated in response to cytokines and oxidative stress [ 79 , 80 ] and activation of the p38 signaling pathway leads to mitochondrial dysfunction and inflammatory responses [ [81] , [82] , [83] , [84] ]. Because a p38 inhibitor blocks mitochondrial dysfunction and inhibits cytochrome c release [ 85 ], it is likely that retinal AIBP not only plays a role in the stabilization of mitochondrial proteins, but also inhibits stress-activated intracellular signaling responses, such as p38 activation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49,50 ] Also, researchers expressed there was a possibility that generated ROS and RNS/NO in tumour cells regulate MMP9 expression and/or activation. [ 51–53 ] Flavonoids/flavones are direct scavengers of ROS and RNS. [ 54 ] Henceforth, it was believed that TMF as a flavone scavenged ROS and RNS free radicals and thereby suppress activation of both STAT3 and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are recognized as key regulatory proteins in oxidative signal transduction. Under physiological conditions, ROS regulate the activity of MAPK to transmit oxidation signals by targeting MAPK phosphatases, members of the PTP family . However, excessive ROS will activate protein phosphatases, causing dysfunction of oxidative signal transduction and exciting the oxidative stress response.…”
Section: Ros Specificity and Selectivitymentioning
confidence: 99%